2023
DOI: 10.1021/acs.jproteome.2c00854
|View full text |Cite
|
Sign up to set email alerts
|

Human Mitochondrial Protein HSPD1 Binds to and Regulates the Repair of Deoxyinosine in DNA

Abstract: The generation of deoxyinosine (dI) in DNA is one of the most important sources of genetic mutations, which may lead to cancer and other human diseases. A further understanding of the biological consequences of dI necessitates the identification and functional characterizations of dI-binding proteins. Herein, we employed a mass spectrometry-based proteomics approach to detect the cellular proteins that may sense the presence of dI in DNA. Our results demonstrated that human mitochondrial heat shock protein 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 54 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Broilers exposed to HS also had lower ATP levels than the control group, as reported by Zhang et al (2018a) . Additionally, Zheng et al (2023) found a positive correlation between ATP levels and mitochondrial DNA ( mtDNA ) number, resulting from mitochondrial dysfunction in the liver. The final stage of the mitochondrial respiration chain involves cyclooxygenase ( COX ) and Cyt-c and impacts the generation of ATP and ROS and their elimination ( Sena and Chandel, 2012 ).…”
Section: Heat Stress Induces Mitochondrial Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations
“…Broilers exposed to HS also had lower ATP levels than the control group, as reported by Zhang et al (2018a) . Additionally, Zheng et al (2023) found a positive correlation between ATP levels and mitochondrial DNA ( mtDNA ) number, resulting from mitochondrial dysfunction in the liver. The final stage of the mitochondrial respiration chain involves cyclooxygenase ( COX ) and Cyt-c and impacts the generation of ATP and ROS and their elimination ( Sena and Chandel, 2012 ).…”
Section: Heat Stress Induces Mitochondrial Dysfunctionmentioning
confidence: 99%
“…The 37 genes in mitochondrial DNA are all essential for regular mitochondrial function, and studies have displayed that mitochondrial dysfunction is accompanied by reduced mtDNA quality ( Zheng et al, 2023 ). This suggests that mitochondrial dysfunction may be a potential reason for the reduced growth performance and feed efficiency detected in heat-stressed broilers ( Chen et al, 2023a ).…”
Section: Mitochondria Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…Inosine, as the deaminated adenosine, leads to A‐to‐G transitions within the DNA sequence, which may accelerate cancer development [21,22]. Notably, hypoxanthine, the nucleobase for deoxyinosine, has been detected as a spontaneous DNA deamination product [23,24].…”
Section: Figmentioning
confidence: 99%
“…To decipher the complexities of gene regulation on the genomic DNA and transcribed RNA, and its impact on human diseases, a new technique is required to identify and analyze such hidden base editing mechanisms. Inosine, as the deaminated adenosine, leads to Ato-G transitions within the DNA sequence, which may accelerate cancer development [21,22]. Notably, hypoxanthine, the nucleobase for deoxyinosine, has been detected as a spontaneous DNA deamination product [23,24].…”
mentioning
confidence: 99%